Predatory publishing: A threat to the credibility of science - Shrestha, Jiban; Subedi, Subash; Timsina, Krishna Prasad (Nepal Journal of Multidisciplinary Research, 2020)
Predatory journals pose a global threat to science. Young scientists and scholars are easy victims of the predatory publications. Predatory publications reduce the accuracy, reliability, and validity of the scientific works published. The predatory publications are worthless, just a waste of time, resources, money, and efforts. Predatory publications undermine the value of legitimate publications. In order to discourage predatory publications, educational and research institutions should set the rules for publication in the journals that must be indexed in web of science, Journal Citation Reports (JCR, Clarivate Analytics, formerly Thomson-Reuters) or other famous scientific databases such as Scopus, DOAJ, PubMed, and MEDLINE. Citation of articles from predatory journals should be discouraged. The students, academics, and researchers should be careful to avoid predatory publications to maintain their credentials.